Balanced Scorecard Based Performance Management: Case Study From PT. Semen Indonesia Distribution - Anindya, Ajrine; Irawan, Valina Sinka (Manunggal Halim Jaya, 2025)
The imbalance between cement supply and consumption in Indonesia has caused consumers' bargaining position to increase, demands to increase, and create fierce competition. One of the marketing functions, namely Place, has the meaning of distributing goods, so that if a company wants to win the business competition, it must be good at planning, implementing and evaluating the distribution system. This study aims to determine how the use of balanced corecard in managing performance management at PT. Semen Indonesia Distribusi using financial, customer, internal process, and learning and growth perspectives. The results of the study show that the process of managing performance management at PT. Semen Indonesia Distribusi begins with determining the strategic targets of each perspective in the balanced scorecard which is outlined in the strategy map. The company needs to compile Key Performance Indicators (KPI) in order to find out the results of these strategic achievements.